Increasing Quiet Compliance by Detained Male Adolescents. (November 2017) - Brogan, Kristen M.; Rapp, John T.; Niedfeld, Amanda M.; Coon, Jodi C.; Everhart Newman, Jan L.; Burkhart, Barry R.
Some adjudicated adolescents receive treatment for their offenses in residential facilities. Detained adolescents' engagement in either low levels of compliant behavior or excess behavior (e.g., swearing, gestures) while following commands from residential personnel may result in decreased opportunities for those youth to access preferred activities. The current study employed nonconcurrent multiple baseline across participants designs to evaluate the effects of a procedure to increase seven detained adolescents' quiet compliance with academic and vocational demands. Results show that problem behavior decreased to zero or near-zero levels for each participant during simulated conditions and suggest that self-control, alone or in combination with a differential reinforcement of low rate behavior for omitting problem behavior, may have been responsible for the behavior changes. We discuss some clinical implications of the findings.